Kritik Nalar Integrasi Keilmuan dI PTKIN: Mengusung Keilmuan Tabot dan Domestifikasi Studi Keislaman Berwawasan Kebangsaan - Moch Iqbal (IAIN Bengkulu, 2020)
This paper examines the scientific design that combines Islam with a national perspective, which the author calls the Tabot’s scientific . Tabot's scientific design is Islam juxtaposed with local wisdom, to produce a wasathiyah (moderate) Islam. So far, the scientific design at PTKIN only reinforces the scientific dichotomy between science and religion. Such as the science of Spider Web, Tree of Science, Twin Tower and others, all carry the integration of religion and science. Islam itself does not recognize this scientific separation. Using library research (literature study), which is a method that is carried out by collecting data and information from books and writings that are related to the research object which is discussed descriptively-analytic through philosophical studies with a qualitative-rationalistic approach . The results of this study are: first, religion and national locality are like two sides of a coin that cannot be separated. Religion does not exist in a cultural vacuum. Rather, religion always includes two inseparable but distinguishable entities, namely normativity and historicity. Second, it is necessary to ground (domestication), downstream science, both religion and science technology according to the needs of the Indonesian people. So far, the science on campus has been more on the ceiling, in the ivory tower rather than manifesting in beneficial social and technological attitudes. Indonesian scientists are more expert in discourse rather than manifesting in praxis and works.Keywords: Criticism, Science, Tabot, Integration, Domestification.